"Otherwise we would not have been here." The story of the Dycha family from the village of Hrušky (Břeclav district) - Schuster, Michal (Romano džaniben, 2020)
The case study focuses on the reconstruction of the life of a Romani family from the South Moravian village of Hrušky since the second half of the 19th century, in the interwar period and especially during WWII, when the family members became victims of Nazi persecution of "gypsies". The study thus contributes to the historical research of the life of specific Romani local communities, families and individuals in the context of the development of a centrally controlled and implemented solution to the "gypsy question" in the Protectorate. The chosen perspective of the study makes it possible to consider coexistence and persecution at the local level and at the same time qualifies the impact of measures at the state level. The author analyzes local preparations and deportations of "gypsies and gypsy half-breeds" to the Auschwitz-Birkenau concentration camp. It addresses the question of how the local inclusion and recognition of Roma by local authorities and institutions could influence and mitigate, at least for some time, their exclusion and categorization, as well as their deportation to a concentration camp, together with the possibility to temporarily or permanently avoid such deportation.